2018
DOI: 10.1136/gutjnl-2016-313498
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota modulate T cell trafficking into human colorectal cancer

Abstract: Gut microbiota stimulate chemokine production by CRC cells, thus favouring recruitment of beneficial T cells into tumour tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
151
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(155 citation statements)
references
References 28 publications
4
151
0
Order By: Relevance
“…In their study on PDAC microbiome, Pushalkar et al (59) found that, although endogenous bacterial dysbiosis triggered immune suppression, Treg differentiation did not differ in PDAC-bearing and WT mice. Similar results were observed in another study (117), where the number of Foxp3 + T cells isolated from the spleen was not different between PBS-and Bifidobacteriumtreated mice, but genes targeted to certain metabolic pathways of Tregs, such as cellular macromolecules and organic substances, were expressed differentially. It remains to be verified whether the involvement of Tregs is the main cause of differential response to immunotherapy.…”
Section: Decreasing Peripherally Derived Tregssupporting
confidence: 88%
“…In their study on PDAC microbiome, Pushalkar et al (59) found that, although endogenous bacterial dysbiosis triggered immune suppression, Treg differentiation did not differ in PDAC-bearing and WT mice. Similar results were observed in another study (117), where the number of Foxp3 + T cells isolated from the spleen was not different between PBS-and Bifidobacteriumtreated mice, but genes targeted to certain metabolic pathways of Tregs, such as cellular macromolecules and organic substances, were expressed differentially. It remains to be verified whether the involvement of Tregs is the main cause of differential response to immunotherapy.…”
Section: Decreasing Peripherally Derived Tregssupporting
confidence: 88%
“…By binding to corresponding CKRs on the target cell membrane, chemokines can induce the targeted migration of target cells (20). The interaction between chemokines released in an abnormal cancer microenvironment and CKRs on the surface of CIK cells is an important factor that affects the tumor-targeted migration ability of CIK cells (21). The concordance between these two variables directly affects the treatment effects of CIK cells (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Further, we have shown recently that specific microbiota, as likely initiators of TLR/MyD88-signalling, are associated with T-cell populations and prognosis in human colorectal cancer. 24 Thus, blocking MyD88 in a therapeutic context might engage anti-tumoral effects of the adaptive immunity. Previously, TLR signaling was reported to induce EMT and tumor malignancy in hepatocellular cancer cell lines, however not for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%